Analysis of High School Students' Creative Thinking Ability in Dynamic Fluid Topics - Irvaniyah, Bintan Nuril; Pandango, Oktavina; Saidan, Mohammad Jazil; Parno (Department of Physics Education, Universitas Mataram, 2025)
Creative thinking ability (CTA) is essential for generating innovative solutions to real-world challenges. This study analyzes high school students' CTA on dynamic fluid topics, focusing on subtopics of flow rate, continuity principle, and Bernoulli's principle. A quantitative survey was conducted with 33 students from a high school in Malang, Indonesia, using a validated essay-based Creative Thinking Ability Test (reliability: 0.880). Descriptive statistics and rubric-based scoring (0–4 scale) categorized CTA levels. Results indicated an overall low CTA (average score: 26.52/100), with flow rate subtopic scoring